Retrospective study on duration of Loading on Marginal Bone Loss Around Dental Implants - Vhanmane, Priyanka; Chauhan, Pranshu; Sahani, Jewel Ipsita; Sahu, Sameer; George, Jaibin; Hemalatha R, Hemalatha R (Journal of Neonatal Surgery, 2025)
Background: Marginal bone loss (MBL) is a critical parameter in evaluating the long-term success of dental implants. Several factors influence MBL, including the timing of functional loading. This study aimed to assess the relationship between the duration of prosthetic loading and marginal bone loss around dental implants in a retrospective cohort. Materials and Methods: A retrospective analysis was conducted on 120 dental implants placed in 75 patients treated between January 2018 and December 2022. Based on the time interval between implant placement and prosthetic loading, implants were grouped into three categories: early loading (<2 months), conventional loading (2–4 months), and delayed loading (>4 months). Digital periapical radiographs taken at baseline (prosthesis placement) and at 12-month follow-up were used to measure marginal bone levels using standardized software. Statistical analysis was performed using ANOVA and Tukey's post hoc test to compare mean MBL among the three groups. Results: The average marginal bone loss after 12 months was 1.42 ± 0.25 mm in the early loading group, 1.10 ± 0.19 mm in the conventional loading group, and 0.86 ± 0.21 mm in the delayed loading group. A statistically significant difference in MBL was observed among the groups (p < 0.001), with the delayed loading group showing the least bone loss. Pairwise comparisons indicated significant differences between early vs. delayed (p < 0.001) and early vs. conventional loading (p = 0.004), but not between conventional and delayed loading (p = 0.067). Conclusion: The timing of functional loading significantly affects marginal bone preservation around dental implants. Delayed loading appears to be associated with reduced bone loss at one year post-restoration. Careful consideration of loading protocols may enhance implant longevity and peri-implant bone stability.